The Desire for Multiple Pregnancy among Patients with Infertility and Their Partners - Md Latar, Ida Lilywaty; Razali, Nuguelis (International Journal of Reproductive Medicine, 2014)
Objective. To study the predictors for desire for multiple pregnancies and the influence of providing information regarding the maternal and fetal complications associated with multiple pregnancies on their preference for multiple pregnancies. Methods. Couples attending an infertility clinic were offered to fill up a questionnaire separately. Following this, they were handed a pamphlet with information regarding the risks associated with multiple pregnancies. The patients will then be required to answer the question on the number of pregnancies desired again. Results. Two hundred fifty three out of 300 respondents completed the questionnaires adequately. A higher proportion of respondents, 60.3% of females and 57.9% of males, prefer singleton pregnancy. Patients who are younger than 35 years, with preexisting knowledge of risks associated with multiple pregnancies and previous treatment for infertility, have decreased desire for multiple pregnancies. However, for patients who are older than 35, with longer duration of infertility, and those patients who have preexisting knowledge of the increased risk, providing further information regarding the risks did not change their initial preferences. Conclusion. Providing and reinforcing knowledge on the risks to mother and fetus associated with multiple pregnancies did not decrease the preference for multiple pregnancies in patients.